Historical biogeography of the termite clade Rhinotermitinae (Blattodea: Isoptera) - Wang, Menglin; Buček, Aleš; Šobotník, Jan; Sillam-Dussès, David; Evans, Theodore A; Roisin, Yves; Lo, Nathan; Bourguignon, Thomas (Molecular phylogenetics and evolution, 2019)
Termites are the principal decomposers in tropical and subtropical ecosystems around the world. Time-calibrated molecular phylogenies show that some lineages of Neoisoptera diversified during the Oligocene and Miocene, and acquired their pantropical distribution through transoceanic dispersal events, probably by rafting in wood. In this paper, we intend to resolve the historical biogeography of one of the earliest branching lineages of Neoisoptera, the Rhinotermitinae. We used the mitochondrial genomes of 27 species of Rhinotermitinae to build two robust time-calibrated phylogenetic trees that we used to reconstruct the ancestral distribution of the group. Our analyses support the monophyly of Rhinotermitinae and all genera of Rhinotermitinae. Our molecular clock trees provided time estimations that diverged by up to 15.6 million years depending on whether or not 3rd codon positions were included. Rhinotermitinae arose 50.4-64.6 Ma (41.7-74.5 Ma 95% HPD). We detected four disjunctions among biogeographic realms, the earliest of which occurred 41.0-56.6 Ma (33.0-65.8 Ma 95% HPD), and the latest of which occurred 20.3-34.2 Ma (15.9-40.4 Ma 95% HPD). These results show that the Rhinotermitinae acquired their distribution through a combination of transoceanic dispersals and dispersals across land bridges.
Keywords: fylogeografie; Isoptera; švábi; Animals; Genetic Variation; Schedorhinotermes; Phylogeny; zvířata; Parrhinotermes; Phylogeography; Cockroaches; fylogeneze; Dolichorhinotermes; genetická variace; Rhinotermes; Genome, Mitochondrial; genom mitochondriální